2022
DOI: 10.3390/su14116591
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Saving Task Scheduling Based on Hard Reliability Requirements: A Novel Approach with Low Energy Consumption and High Reliability

Abstract: With the increasing complexity of application situations in multi-core processing systems, how to assure task execution reliability has become a focus of scheduling algorithm research in recent years. Most fault-tolerant algorithms achieve hard reliability requirements through task redundancy, which increases energy consumption and contradicts the concept of sustainable development. In this paper, we propose a new algorithm called HDFE (Heterogeneous-Dag-task-fault-tolerance-energy-efficiency algorithm) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this section, we discuss the mathematical model of heterogeneous multi-core processor with DVFS [8]. For the heterogeneous multi-core processor model studied in this paper, we make the following assumptions :(1) Priority and constraint dependence between tasks.…”
Section: Modelmentioning
confidence: 99%
“…In this section, we discuss the mathematical model of heterogeneous multi-core processor with DVFS [8]. For the heterogeneous multi-core processor model studied in this paper, we make the following assumptions :(1) Priority and constraint dependence between tasks.…”
Section: Modelmentioning
confidence: 99%
“…By carrying out fault diagnosis research, unit faults can be found in time to ensure the unit's safe operation and prolong the unit's service life. In addition, fault diagnosis research can also improve the reliability and efficiency of unit operations and reduce the maintenance costs and energy consumption, which is also significant for the sustainable development and utilization of hydropower energy [2,3].…”
Section: Introductionmentioning
confidence: 99%